Audiovisual accessibility and translation practices in Spanish cinema and theatre: From regulations to screen and stage - Enríquez-Aranda, Mercedes; Varela-Salinas, María José (Skase. Journal of Translation and Interpretation, 2021)
In the last decade, very specific regulations have been developed in Spain regarding media accessibility. Public institutions and academic initiatives are also working to promote media accessibility. Regulative pillars for the implementation of accessibility practices in the audiovisual media are a reality in Spain. There comes the time to analyse if the practices correspond to their demands. This paper presents the results derived from the study of audiovisual accessibility and translation practices implemented in the cinemas and theatres of Malaga (Spain), Mediterranean paradigm of multilingual cultural offer, during the first quarter of 2019. The audiovisual offer, the accessibility and translation practices used, the technical means applied for the display of the final products and the languages involved in the process are studied consequently. The final results may contribute to foster social inclusion and fill in a theoretical gap in academic research.
Keywords: Medios audiovisuales - Accesibilidad; Accesibilidad; Inclusión; Audiovisual translation; Media accessibility; Social inclusion; Theatre; Cinema